PET-CT for characterising TB infection (TBI) in immunocompetent subjects: a systematic review - Kim, Jee Whang; Munavvar, Rayhan; Kamil, Anver; Haldar, Pranabashis (Journal of medical microbiology, 2023)
Introduction. There is emerging evidence of a potential role for PET-CT scan as an imaging biomarker to characterise the spectrum of tuberculosis infection (TBI) in humans and animal models.Gap Statement. Synthesis of available evidence from current literature is needed to understand the utility of PET-CT for characterising TBI and how this may inform application of PET-CT in future TBI research.Aim. The aims of this review are to summarise the evidence of PET-CT scan use in immunocompetent hosts with TBI, and compare PET-CT features observed in humans and animal models.Methodology. MEDLINE, Embase and PubMed Central were searched to identify relevant publications. Studies were selected if they reported PET-CT features in human or animals with TBI. Studies were excluded if immune deficiency was present at the time of the initial PET-CT scan.Results. Six studies - four in humans and two in non-human primates (NHP) were included for analysis. All six studies used 2-deoxy-2-[18F]fluoro-d-glucose (2-[18F]FDG) PET-CT. Features of TBI were comparable between NHP and humans, with 2-[18F]FDG avid intrathoracic lymph nodes observed during early infection. Progressive TBI was characterised in NHP by increasing 2-[18F]FDG avidity and size of lesions. Two human studies suggested that PET-CT can discriminate between active TB and inactive TBI. However, data synthesis was generally limited by human studies including inconsistent and poorly characterised cohorts and the small number of eligible studies for review.Conclusion. Our review provides some evidence, limited primarily to non-human primate models, of PET-CT utility as a highly sensitive imaging modality to reveal and characterise meaningful metabolic and structural change in early TBI. The few human studies identified exhibit considerable heterogeneity. Larger prospective studies are needed recruiting well characterised cohorts with TBI and adopting a standardized PET-CT protocol, to better understand utility of this imaging biomarker to support future research.Introduction. There is emerging evidence of a potential role for PET-CT scan as an imaging biomarker to characterise the spectrum of tuberculosis infection (TBI) in humans and animal models.Gap Statement. Synthesis of available evidence from current literature is needed to understand the utility of PET-CT for characterising TBI and how this may inform application of PET-CT in future TBI research.Aim. The aims of this review are to summarise the evidence of PET-CT scan use in immunocompetent hosts with TBI, and compare PET-CT features observed in humans and animal models.Methodology. MEDLINE, Embase and PubMed Central were searched to identify relevant publications. Studies were selected if they reported PET-CT features in human or animals with TBI. Studies were excluded if immune deficiency was present at the time of the initial PET-CT scan.Results. Six studies - four in humans and two in non-human primates (NHP) were included for analysis. All six studies used 2-deoxy-2-[18F]fluoro-d-glucose (2-[18F]FDG) PET-CT. Features of TBI were comparable between NHP and humans, with 2-[18F]FDG avid intrathoracic lymph nodes observed during early infection. Progressive TBI was characterised in NHP by increasing 2-[18F]FDG avidity and size of lesions. Two human studies suggested that PET-CT can discriminate between active TB and inactive TBI. However, data synthesis was generally limited by human studies including inconsistent and poorly characterised cohorts and the small number of eligible studies for review.Conclusion. Our review provides some evidence, limited primarily to non-human primate models, of PET-CT utility as a highly sensitive imaging modality to reveal and characterise meaningful metabolic and structural change in early TBI. The few human studies identified exhibit considerable heterogeneity. Larger prospective studies are needed recruiting well characterised cohorts with TBI and adopting a standardized PET-CT protocol, to better understand utility of this imaging biomarker to support future research.